Hospital Quality Improvement Interventions, Statewide Policy Initiatives, and Rates of Cesarean Delivery for Nulliparous, Term, Singleton, Vertex Births in California. Issue 1 (23rd March 2022) - Rosenstein, M.G.; Chang, S.C.; Sakowski, C.; Markow, C.; Teleki, S.; Lang, L.; Logan, J.; Cape, V.; Main, E.K.
Abstract : ( JAMA . 2021;325:1631–1639. doi: 10.1001/jama.2021.3816. PMID: 33904868) Cesarean delivery (CD) rates are concerningly high for women with nulliparous, term, singleton, vertex (NTSV) deliveries, and ongoing racial disparities suggest hospital culture, policies, and attitudes play a role. California Maternal Quality Care Collaborative (CMQCC) is a collaborative that seeks to improve maternity care and outcomes and reduce the CD rate of NTSV births in the state of California. This study aimed to evaluate California's cesarean delivery rate for NTSV births given the new CMQCC initiative employed to reduce that number.